Introduction to the mini special issue: understanding governance in Indonesia - Sutiyono, Wahyu; Pramusinto, Agus; Prasojo, Eko (2018)
This is the first of a series of mini special issues of Policy Studies which investigate different aspects of governance in developing areas. This issue investigates the changing nature of Indonesian governance focusing on: (1) the allocation of roles and responsibilities between different tiers of governance at the centre of the political domain; (2) the implementation of the conditions of ASEAN Economic Community reform; and (3) the role of academic administrative entrepreneurs in facilitating processes of administrative change. It draws on the multi-level governance literature developed in the study of the European Union providing unique insights into the emergence of new modes of governance in a period of democratic transition paying specific attention to the interaction between domestic and international sources of policy change. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.